Innovations in 3D geo-information sciences - Isikdag, Umit (Lecture Notes in Geoinformation and Cartography,, 2014)
3D GeoInfo aims to bring together international state-of-the-art research and facilitate the dialogue on emerging topics in the field of 3D geo-information. The conference offers an interdisciplinary forum in the fields of 3D data collection and modeling; reconstruction and methods for 3D representation; data management for maintenance of 3D geo-information or 3D data analysis and visualization. The book covers  the best papers from 3D GeoInfo held in Istanbul in November 2013.